Highly Time-Resolved Elemental Source Apportionment at a Prague Urban Traffic Site - Laurence C. Windell; Petra Pokorná; Jaroslav Schwarz; Petr Vodička; Philip K. Hopke; Naděžda Zíková; Radek Lhotka; Jakub Ondráček; Petr Roztočil; Michal Vojtišek; Vladimír Ždímal (Aerosol and Air Quality Research)
Abstract Positive Matrix Factorization was used for source apportionment of 2-hour online metals (Xact625i; PM2.5) and elemental and organic carbon (EC/OC analyser; PM1) data at an urban traffic site in Prague, Czech Republic, for two month-long periods in spring (February–March) and winter (November–December), 2020 (400 samples). Five factors were obtained for spring: Local heating (39%), Soil/road dust (21%), Secondary inorganic aerosol (20%), Traffic (12%), and Road salt (9%), while four factors were resolved for winter: Local heating (20%), Soil/road dust (31%), Secondary inorganic aerosol (SIA; 36%), and Traffic (13%). Aside from SIA, the sources were of local origins. Air mass back trajectories calculated by HYSPLIT and concentration weighted trajectories (CWT) were used to identify long-distance sources. Greater PM concentrations during winter (~3 times greater) were attributed to both lower boundary layer heights and more abundant air masses from Central Europe, compared to more marine air masses during spring.